Heterocontrole dos teores de flúor nas águas de abastecimento público de Fortaleza, Ceará - Camurça, Valquiria Vieira (2008)
The importance of the action of fluoride in the control of dental caries has been proved internationally over the period of many years, such that the fluoridation of public water supply has been accepted as a key control method. It is not enough, however, to simply apply fluoride to water; it is also necessary to assure that the population receives the appropriate quantity of the element. For this to happen, a surveillance system must be in place with the objective of monitoring the fluoridation of public water sources (heterocontrol). Within this context, the objective of this study is to evaluate the heterocontrol of fluoride levels in the water supply of Fortaleza, Ceará, through a descriptive, observational, longitudinal study. Towards this end, qualitative and quantitative analyses were employed. In the qualitative approach, we sought to understand the ways in which Fortaleza controls its water quality with respect to fluoride levels, describing the methodology used by the Environmental Health Surveillance System of Fortaleza for heterocontrol. For data collection, a semi-structured interview with a script was used and applied to the technicians responsible for heterocontrol. The interviews were conducted by the researcher, using a recorder to tape the answers given by the interviewees. In relation to the quantitative approach, the study sought to determine the fluoride levels in the Fortaleza public water supply according to the Municipal Environmental Surveillance Sector, and subsequently to compare these results to those of the Ceará Water Works (CAGECE), verifying the existence of under or over dosage. The period of January to November 2006 was defined to evaluate the data of the two institutions, using Student’s t-test to compare the averages of fluoride levels taken by Fortaleza Environmental Surveillance and CAGECE and to compare the averages with the standard values of 0.6 ppm of fluoride (minimum value) and 0.8 ppm (maximum value). Following the qualitative analysis, it was verified that there exists a structured system in the municipality of Fortaleza to collect, impound, store and analyze water samples in order to determine fluoride levels as well as the geographic distribution of the water collection sites and the training of those responsible for sample impounding. However, it was observed that fewer samples are analyzed per month than is ideal. As for the quantitative analysis, Fortaleza Environmental Surveillance found elevated fluoride levels over the period under study with an average of 0.8532 ppm and 53.6% of analyses above the accepted limits, thereby increasing the risk of dental fluorosis. Differences in the analyses of Fortaleza Environmental Surveillance and CAGECE were also encountered over this period, suggesting the need for more analysis to determine the true fluoride concentration in the city’s water supply. We conclude that the capital city of Ceará does have a methodology for heterocontrol, based on its scientific and technical documents. However, there are inherent flaws in the recent implementation of fluoride surveillance in the public water supply. We also conclude that there is no consensus between the data of the two institutions researched, thus making it necessary to undertake new analyses to identify the correct fluoride levels in the Fortaleza water supply and definitively establish the levels to be supplied to the general public.